Tulisan-tulisan tentang Borobudur: Menempatkan naskah Jawa Modern Awal dalam produksi pengetahuan arkeologi di Indonesia - Panggah Ardiyansyah (Balai Arkeologi Yogyakarta, 2022)
As a heritage site today, Borobudur is arguably constructed from stories of ancient grandeur, regrettable loss, and colonial rescue, infused with lingering aesthetics of colonial construction. This paper discusses the historical deconstruction of the process of historical knowledge production of Borobudur by analysing the Babad Tanah Jawi manuscript produced from the late 18th century to the early 19th century by Javanese courts. The result shows that during the Early Modern Java, Borobudur held significant spiritual quality for the local communities, unlike the previous interpretation by the colonial authorities.